Explaining The Changes of Agriculture Land Prices In Lithuania - Rutkauskas, Virgilijus; Gudauskaitė, Laura (Ekonomika, 2018)
This article investigates the recent changes of agricultural land prices in Lithuania and quantitively assesses the most important factors affecting it. Land is one of the main scarce resources and it distinguishes itself among others by the inelasticity of price change to quantity, meaning that the changes in land prices are affected by demand and in very limited extend by supply. Taking this into account, it is important – from the practical as well as the theoretical points of view – to know these factors and, if needed, take regulatory measures. As the case of Lithuania suggests, the recent rapid growth of land prices is mainly driven by general economic performance (GDP), EU and national financial support provided to the Lithuanian agriculture sector and the regulation of agriculture food prices (the setting of purchase prices).